EU cohesion policy, past and present: Sustaining a prospering and fair European Union? - Christiane Krieger-Boden (Kiel Institute for the World Economy (IfW), 2016)
In 2015, the EU regional / cohesion policy has passed its 40th anniversary. During this time, it has undergone various manifestations with ever-changing objectives. It started as a mixture of structural and regional policy aimed at reducing regional economic disparities within the Union. Since 2000 at latest, however, cohesion policy has been subordinated to a growth and competitiveness strategy and has undergone a substantial re-definition of objectives and principles. At the background of a potential conflict between growth and cohesion objectives, i.e., between efficiency and equality, the paper finds discrepancies between asserted intentions and actual practise of cohesion policy. On this ground, the paper argues for a return to a less ambitious, more basic-needs oriented cohesion policy.
Keywords: H7; R5; 330; cohesion; regional policy; growth policy; EU Structural Funds